MMPI in clinical psychodiagnostic: |results of comparative research study with neurotics, schizophrenics and psychotic depressives - Özoğuztan, Bürçin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1984., 1984)
The purpose of this study is to investigate the· effectiveness of Minnesota Multiohasic Personality Inventory in psychodiagnostic· classification and to find out if there is sex differences in resoonding to soeciaf clinical scales of the MMPI. In this oresent study three diagnostic categories were comoared: neurotics, schizophrenics and osychotic deoressives. The 60 subjects were selected from ''Bakırköy State Mental Hospital" It was hypothesized that, the neurotic patients will have higher scores on Hyoocondriasis (Hs) and Hysteria (Hy) scales: the schizophrenic patients will have higher scores on Paranoia (Pa), Psychasthenia (Pt), Schizophrenia (Sc) and Mania (Ma) scaler. It was also hypothesized that the psychoti depressives will have higher scores on Depression (D) and Socia Introversion (Si) scales. Concerning with the sex differences, it was hypothesized that females will have higher scores on Hysteria (Hy) and Hypomania (Ma) scalesi and males will have hiqher scores on Hypocondiasis (Hs) and Psychopathic deviate (Pd) scales. Also,some demographic factors were obtained by giving a questionnaire such as age, education, education of the mother and father and the presedence. The results show that, as it was hypothesized the neurotic patients have higher scores on Hysteria and Hyoocondria scales. The results concerning with schizophrenic patients showed that, they have signiciantly higher scores on Paranoia, Psychasthenia and Schizoohrenia scales. It was also hypothesized that the schizoohrenic oateants will have higher scores on Hypomania scale: but the results indicate that the neurotic patients have higher scores on this scale. This can be due to the fact that the schizoohrenic subjects were not classified into categories such as acute, chronic and etc. The majority of then were chronic schizophrenics. The results also indicate that the psychotic depressive patients have significantly higher scores on Depressio and Social Introversion scales, as it was expected. Concerning with the sex differences, the males have significantly higher scores on Hyoocondria scale as it was hysothesized. On the Hysteria scale no sionificant sex difference were found. Tne results show that females have significantly higher scores on psychopathic deviate and Hypomania scale.
Keywords: Minnesota Multiphasic Personality Inventory.; Psychodiagnostics.